ANALISIS WACANA IKLAN PRODUK KECANTIKAN BERUPA LIPSTIK PADA TELEVISI BERDASARKAN STRUKTUR DAN FUNGSI BAHASA - Rahmadani Linda Fadillah (LPPM STKIP PGRI Bandar Lampung, 2020)
This research describes the structure and function of Lipstick Beauty Product advertisements on television. This study uses a discourse analysis approach, this type of research is qualitative. The method used in this research is descriptive analysis. The data source of this research is in the form of Lipstick Beauty Product advertisements on television, which contains the structure and function of the advertising language.The results of the study describe the structure of lipstick beauty product advertisements on television consisting of language functions contained in food and beverage product advertisements on television including: (a) information functions, (b) persuasive functions and to form a positive image of the product to potential consumers.